Agriculture organic wastes fermentation CO2 enrichment in greenhouse and the fermentation residues improve growth, yield and fruit quality in tomato. (1st December 2020) - Hao, Peng-Fei; Qiu, Cheng-Wei; Ding, Guohua; Vincze, Eva; Zhang, Guoping; Zhang, Yongsong; Wu, Feibo
Abstract: The concern about fossil fuel shortage and environmental pollution highlighted the necessity to improve the output performance in facility agriculture. We investigated the influence of a climate-smart agricultural production system, namely agriculture organic waste fermentation CO2 enrichment technology (AOWF + CO2 ) on greenhouse tomato production and the effect of fermentation residues from AOWF + CO2 . AOWF + CO2 exhibited positive effect on tomato growth, yield and fruit quality. Soluble sugar, lycopene and carotenoid contents in tomato fruits increased by 24.1%, 53% and 129%, respectively, while the nitrate content decreased by 10.7% when compared with control. The metabolome and proteome studies revealed significant up-regulation of secondary metabolisms, and the differentially expressed proteins (DEPs) were significantly enriched in purine, pyrimidine and linoleic acid metabolism pathways. The fermentation residues also significantly increased tomato growth, yield and fruit quality. It was estimated that each hectare greenhouse furnished with AOWF + CO2 could at least reduce 17951.5 kg CO2eq. emission, and store 5314.5 kg CO2eq. in soil. In conclusion, AOWF + CO2 and its residues recycling could accelerate tomato growth and productivity. This demonstrates a new climate-smart agriculture approach of reutilizing agricultural organic wastes to improve the sustainability of ecosystem. Graphical abstract: Image 1 Highlights: A climate-smart agricultural production: agriculture organic wastes fermentation CO2 enrichment (AOWF + CO2 ) in greenhouse. Both AOWF + CO2 and fermentation residues improved greenhouse tomato growth, yield and fruit quality. Positive effects of AOWF + CO2 first mechanized by metabolomic and proteomic studies. Fermentation residues replaced parts of chemical fertilizer and store carbon to soil. AOWF + CO2 efficiently utilized agricultural organic wastes, reduced carbon emission.